Training of advanced practice nurses in oncology for the best care: a systematic review - Franciane Schneider; Silvana Silveira Kempfer; Vânia Marli Schubert Backes (SciELO, 2021)
ABSTRACT Objective: To search for evidence on the training of advanced practice nurses, through clinical practice and nursing care with cancer patients. Method: Systematic review, searching the databases: MEDLINE-PubMed, LILACS, Web of Science, Scopus, CINAHL and Cochrane CENTRAL. A manual search of the reference list and Google Scholar was also carried out. To assess the methodological quality of the studies, the following tools were used: Cochrane Collaboration Risk of Bias Tool (RoB 1) for randomized controlled trials and Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) for quasi-experimental studies. Results: A total of 12 experimental studies were identified. The main intervention identified in the studies was educational guidance. The studies showed improvement in pain control or other symptoms related to disease and/or treatment, satisfaction and improvement in the quality of life of cancer patients. Conclusion: It is observed that there are studies that demonstrate the value of advanced practice nursing in oncology, through differentiated clinical training and advanced professional performance. Registration number of the systematic review: CRD42018098906.